Connecting the dots to find the missing link in oral carcinoma - Yash P. Merchant, MDS, FRCS (UK) (Oral Oncology Reports)
Transformation of an oral potentially malignant lesion to frank carcinoma can be considered a continuum due to the interplay of variables related to the host and environmental carcinogen exposure. Tumor populations should not be viewed as isolated cells but comprehended with the micro-environment. The seed and soil theory certainly needs revisiting.